Mapping Landslide Disaster-Prone Areas As An Effort To Develop Semongkat Geotourism In Sumbawa - Pramudya Bagas Utama; Sayidatina Hayatuzzahra; Dedy Dharmawansyah; Fazal Shinwary Revanka; Nisa Nursahida; Angga Satria Adi (Badan Pelaksana Rinjani-geopark Rinjani Lombok, 2024)
Sumbawa Island is a tourist destination because it offers still well-preserved natural beauty. Semongkat geotourism is one of the tour sites visited by many local or foreign tourists located in the north of Batulanteh District, Sumbawa Regency, West Nusa Tenggara Province (Coordinate Latitude -8.574251° SL, Longitude 117.313315° EL), including a hilly area with an altitude of 450 meters above sea level, densely-forested, and well-preserved maintained area. The area is an ecosystem rich in flora and fauna, including the bondol eagle and the koakiau bird which are endangered and protected by law. The problem is that lots of landslides still occur on the access to the area, posing thus risks to passengers and motorists. The data collection method used is to mapping landslide-prone areas with controlling and driving aspects, then make a landslide-prone map to show which areas are categorized as landslide-prone areas. It is important, therefore, to map landslide-prone areas so that mitigation measures can be implemented to ensure a safer life for local people and tourists, a better environment and ecosystem as well as a safer, and also increased geotourism in Semongkat.